Menerapkan Etika Dan Etos Kepemimpinan Yesus Kristus Yang Aktual Dalam Organisasi Gereja - Iskandar, Iskandar; Mustakim, Mustakim (Sekolah Tinggi Teologi Immanuel Sintang Kal-Bar, 2021)
Applying the actual ethics and leadership ethos of Jesus Christ in church organizations. Christian leadership that is very much needed today is a responsible leader, always putting hope in Jesus Christ in the organization as a shepherd leading the congregation, and having ethics and ethos. In leading, one must have good integrity in serving. The methodology used is literature research using primary sources from books, journals and previous research as a source of study. The primary data is then analyzed and synthesized to become the novelty discussed in this study. So the orientation in empowering leadership is an effort to help individuals who are led reach a better stage so that it is more lightening compared to Musa's single leadership. The principles of leadership discussed include delegating leadership, increasing responsibility, increasing capacity, practicing independence and being willing to learn and be taught. Thus, this leadership can bring wider influence and create empowered individuals, not depending on a particular situation or organization. Today's leadership succession requires forming leaders who excel in facing competition, innovation, and leadership succession skills that can be realized in empowering leadership.